Theoretical Physics 9 Fundamentals of Many-body Physics - Nolting, Wolfgang (Springer International Publishing, 2018)
This textbook addresses the special physics of many-particle systems, especially those dominated by correlation effects. It develops modern methods to treat such systems and demonstrates their application through numerous appropriate exercises, mainly from the field of solid state physics. The book is written in a tutorial style appropriate for those who want to learn many-body theory and eventually to use this to do research work in this field. The exercises, together with full solutions for evaluating one's performance, help to deepen understanding of the main aspects of many-particle systems. This revised second edition presents new sections on the finite-temperature Matsubara formalism, in particular with respect to Dyson equation, the Hartree-Fock approximation, second order perturbation theory, spin density waves, Hubbard model, Jellium model, quasi particles, Fermi liquids and multi particle Matsubara functions. Completing the outstanding Theoretical Physics series, this book will be a valuable resource for advanced students and researchers alike.